Mission and Migration: Epistemological Tension in Two Research Fields - Astrid Krabbe Trolle (Religions)
In this article, I argue that the research fields of migration and mission navigate similar tensions between normative interests and descriptive categories. With its biblical legacy, mission is actualized in a variety of ways within the contemporary paradigm of mission everywhere and for every Christian. In the field of mission, a history of colonialization and de-colonialization has resulted in disciplinary struggles over the content and inclusiveness of mission as a scientific category. In the field of migration, political interests related to nation-state regimes often influence research, resulting in several migration scholars pushing back and placing their analytical object—the migrant—as a suffering subject in need of protection. However, tensions between the notions of prescriptive/descriptive and political/ethical produce interesting concepts, and one of them is reverse mission. Applying reverse mission to the case study of the Catholic Church in the Philippines and Denmark, I conclude that different forms of mission (missionary discipleship and domestic mission) are a powerful leit motif for global church work.